2018
DOI: 10.9734/csji/2018/41080
|View full text |Cite
|
Sign up to set email alerts
|

Background Correction Method for Determination of Ascorbic Acid in Baobab Fruit Pulp Using Direct UV Spectrophotometry

Abstract: Herein a background correction method has been utilized for the estimation of ascorbic acid in baobab (Adansonia digitata L.) fruit pulp using direct UV spectrophotometry. The background correction based on catalytic oxidation of the acid by copper (II). EDTA was used to correct the absorption due to copper (II). The absorbance and remained essentially constant at 267 nm at pH range from 6 to 8, with highest absorption at pH 6. The calibration graph was linear up to 20 μg ml -1 of ascorbic acid, correlation co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 9 publications
2
3
0
Order By: Relevance
“…Analyses of its proximate composition has showed low mean moisture content, crude fat, and crude protein and high mean crude ash, crude fber, and total carbohydrate content (Table 6). Higher crude fber and total carbohydrate contents as compared to other proximate components were also reported in studies carried out in the Sudan and elsewhere [29][30][31]. Te mean gross energy value observed in the current study was also comparable to results of other research studies that reported 202.9 to 357.3.9 kcal/ 100 g dry weight [31,32].…”
Section: Physicochemical Properties and Proximate Composition Ofsupporting
confidence: 90%
See 1 more Smart Citation
“…Analyses of its proximate composition has showed low mean moisture content, crude fat, and crude protein and high mean crude ash, crude fber, and total carbohydrate content (Table 6). Higher crude fber and total carbohydrate contents as compared to other proximate components were also reported in studies carried out in the Sudan and elsewhere [29][30][31]. Te mean gross energy value observed in the current study was also comparable to results of other research studies that reported 202.9 to 357.3.9 kcal/ 100 g dry weight [31,32].…”
Section: Physicochemical Properties and Proximate Composition Ofsupporting
confidence: 90%
“…Higher crude fber and total carbohydrate contents as compared to other proximate components were also reported in studies carried out in the Sudan and elsewhere [29][30][31]. Te mean gross energy value observed in the current study was also comparable to results of other research studies that reported 202.9 to 357.3.9 kcal/ 100 g dry weight [31,32]. Tis is due to the high total carbohydrate content.…”
Section: Physicochemical Properties and Proximate Composition Ofsupporting
confidence: 89%
“…The nitric oxide radical scavenging (NOS) activities of the extracts were determined according to the method described by Erwa and coworkers[ 29 ]. A 1.0 mL of 10 mM sodium nitroprusside in phosphate-buffered saline was mixed with 1.0 mL pulp extract of different concentrations (i.e., 100, 250, 500, 750, and 1,000 μ g/mL for the aqueous extract and 50, 100, 150, 200, and 250 μ g/mL for the methanol extract) and incubated at 25°C for 180 min.…”
Section: Methodsmentioning
confidence: 99%
“…Nitric Oxide Scavenging Activity. Te nitric oxide radical scavenging (NOS) activities of the extracts were determined according to the method described by Erwa and coworkers[29]. A 1.0 mL of 10 mM sodium nitroprusside in phosphate-bufered saline was mixed with 1.0 mL pulp extract of diferent 2 (10.0 mmol/L) and was left for 1 h. Ten, 2.0 mL cold thiobarbituric acid (10 g/L) and 2.0 mL HCl (25%) were sequentially added to each of the reaction mixtures.…”
mentioning
confidence: 99%
“…Due to its nutritional profile (Anoh, 2021), baobab has recently been described as a super fruit (i.e., rich in vitamins, fatty acids and minerals). In the past, comprehensive studies on the nutritional properties of baobab fruit pulp and seed has previously been published (Karungamye and Murthy, 2017), the nutritional value of baobab was only briefly discussed with the focus on the mineral composition of baobab fruit pulp (Erwa et al, 2018;Acham et al, 2020). Baobab pulp has very little iron and is a poor source of manganese, but is rich in calcium (Deconinck, 2020).…”
Section: Introductionmentioning
confidence: 99%